The impact of persistent pediatric obstructive sleep apnea on the Quality of Life of Patients' families. (February 2020) - Bergeron, Mathieu; Duggins, Angela L.; Cohen, Aliza P.; Leader, Brittany A.; Ishman, Stacey L.
Abstract: Objectives: To (1) quantify the quality of life (QOL) for families of children affected by persistent obstructive sleep apnea (OSA), and (2) assess factors contributing to the negative impact of OSA on families. Methods: Prospective case series in a multidisciplinary upper airway center at a tertiary pediatric institution. Our study included patients with persistent OSA referred to our clinic from 2014 to 2016. Both patients and their families completed validated questionnaires assessing QOL and OSA symptoms, including the Family Impact Questionnaire (FIQ), Pediatric Sleep Questionnaire, the Pediatric Quality of Life Inventory, the OSA-18, and the Epworth Sleepiness Scale. Results: Families of 67 patients were included. The mean patient age was 12.5 (95%CI 11.9–13.1); 23 (34.3%) were female, and the mean BMI percentile was 80.2 (95%CI 73.6–86.8). The single most common comorbidity was Down syndrome (45.6%). The mean obstructive apnea-hypopnea index was 9.7 ± 10.3 events/hour. A significant association exists between OSA severity and 18 FIQ negative subscore ( P < 0.001). Financial impact was the primary negative concern for parents of patients with OSA compared to those without OSA ( P = 0.03). There were no other significant differences between those with and without OSA. Conclusions: There was a significant correlation between persistent OSA severity and the FIQ negative impact of disease score on patients' families. Concern regarding financial burden was more common for families of children with OSA than for those without OSA. This suggests that targeted interventions, particularly regarding the financial burden of persistent OSA diagnosis and management, may provide some relief to families.